Informational interaction service-simulating test implementation peculiarities of the Internet of things - Selishchev O.V.; Zolotareva T.A.; Voronin I.V. (E3S Web of Conferences, 2020)
This article discusses the technology of building sensor networks. On the basis of the article there is an example of the servicesimulating test for the informational interaction of the Internet of things. The probabilistic-and-time characteristic of the informational interaction of the Internet of things is evaluated. This factor enhances the quality of computer network service. The article also considers a number of tasks, allowing us to build optimal modes of sensor networks functioning. A probabilistic model that allows us to evaluate absolute and probabilistic characteristics of informational interaction is built.